Improving the Wear and Corrosion Resistance of Maraging Part Obtained by Cold Gas Spray Additive Manufacturing - Rodolpho F. Vaz; Alessio Silvello; Vicente Albaladejo; Javier Sanchez; Irene García Cano (Metals, 2021)
The use of the cold gas spray (CGS) process as a metal additive manufacturing (MAM) technique for metallic part production has been deeply studied recently, mainly due to its advantages over other MAM techniques. CGS MAM is a high-productivity technique with a very low level of particle oxidation, microstructural changes, phase transformations, or deleterious residual thermal stresses in the part. The use of CGS MAM to produce maraging parts represents a gain for the industry by saving machining time and preventing raw material waste. Its wear resistance and corrosion behavior were evaluated in this work and were compared with cermet coatings deposited by high-velocity oxy-fuel (HVOF) on the CGS MAM maraging. This work presents the innovative and effective combination of different thermal spraying processes and materials to obtain MAM maraging parts with higher wear resistance, evaluating abrasion, sliding, and water erosion wear types.